2011
DOI: 10.1094/pdis-04-11-0333
|View full text |Cite
|
Sign up to set email alerts
|

Pathotype IV, a New and Highly Virulent Pathotype of Didymella rabiei, Causing Ascochyta Blight in Chickpea in Syria

Abstract: The causal agent of Ascochyta blight disease of chickpea (Cicer arietinum L.) is highly variable because of the presence of a sexual phase (Didymella rabiei). There is also selection pressure on the pathogen due to wide adoption of improved resistant chickpea cultivars in some countries. The pathogen is able to produce pathotypes with specific virulence on particular cultivars. Three pathotypes, I, II, and III, have been reported (3). In this study, we confirmed the presence of a new and highly virulent pathot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 0 publications
2
50
1
Order By: Relevance
“…SSR marker ArH05T was recently reported to amplify Syrian pathotypes III and IV specific bands [4] while in our study two other SSR markers (ArA06T and ArH02T) also differentiated Syrian pathotypes III from IV but unable to distinguish PAR from SAR (Figure 2a). On the other hand the URP primers were highly polymorphic and not only differentiated least aggressive pathotype I (PAR 4) from rest of highly aggressive pathotypes III and IV but also differentiated PAR from SAR (Figure 2b).…”
Section: Methodscontrasting
confidence: 49%
See 2 more Smart Citations
“…SSR marker ArH05T was recently reported to amplify Syrian pathotypes III and IV specific bands [4] while in our study two other SSR markers (ArA06T and ArH02T) also differentiated Syrian pathotypes III from IV but unable to distinguish PAR from SAR (Figure 2a). On the other hand the URP primers were highly polymorphic and not only differentiated least aggressive pathotype I (PAR 4) from rest of highly aggressive pathotypes III and IV but also differentiated PAR from SAR (Figure 2b).…”
Section: Methodscontrasting
confidence: 49%
“…Pathotype variability is necessary to select the appropriate pathotype for screening genotypes in resistance breeding programme [2]. Differentiation of Ascochyta rabiei (AR) into 3 classes (pathotype I, II and III) was reported in Syria and has been widely accepted [3] and recently highly aggressive pathotype IV has been reported by Imtiaz et al [4]. In Pakistan three pathotypes were also identified by Jamil et al [5] and Ali et al [6] using chickpea differential genotypes (ILC1929, ILC482 and ILC3279) and (Spanish white, Dwelley and ICC12004) respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chickpea sowing during early spring could expose the crop to terminal heat and moisture stress. Although farmers in Syria have widely adopted early winter (December) sowing of chickpea, some of them have started sowing their chickpea in early (January) mainly due to weed problem and as a precautionary measure to avoid high Ascochyta blight disease pressure that affects chickpea due to the appearance of new virulent pathotypes of D. rabiei (Imtiaz et al 2011). Though variability in wilt incidence was observed across locations and seasons, our results clearly showed that early sowing can provide good yield.…”
Section: Discussionmentioning
confidence: 67%
“…A new A. rabiei pathotype (pathotype IV) was reported in Syria that is capable of affecting the highly resistant chickpea genotypes (ICC-12004 and ICC-3996) known for their resistance to pathotypes I, II and III. Breeding materials at ICARDA are being screened against this new pathotype IV, and so far low levels of resistance have been observed [37,38]. High genetic diversity has also been reported from USA, Tunisia and Canada where popular varieties have become susceptible to new aggressive pathotypes [26][27][28].…”
Section: Pathogen Variabilitymentioning
confidence: 99%